2017
DOI: 10.1111/jep.12698
|View full text |Cite
|
Sign up to set email alerts
|

Promoting resource stewardship: Reducing inappropriate free thyroid hormone testing

Abstract: Inappropriate testing of free thyroid indices occurs frequently. The implementation of a reflex fT4 strategy after education was feasible in reducing overall testing by 49% and was effective in promoting resource stewardship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…TSH is a sensitive assay that allows for accurate evaluation of thyroid function and is often the only test required for screening thyroid dysfunction and managing hypothyroidism . Despite this, studies have shown that ordering free thyroid hormones is common but often inappropriate . Reduction of excess TFTs could offer a distinctive opportunity to assist in stemming the tide of rising healthcare costs.…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…TSH is a sensitive assay that allows for accurate evaluation of thyroid function and is often the only test required for screening thyroid dysfunction and managing hypothyroidism . Despite this, studies have shown that ordering free thyroid hormones is common but often inappropriate . Reduction of excess TFTs could offer a distinctive opportunity to assist in stemming the tide of rising healthcare costs.…”
Section: Introductionsupporting
confidence: 92%
“…These results indicate that providers at our institute are often relying on free thyroid hormones as an adjunct to TSH for screening or management of thyroid disorders. These findings are largely consistent with known literature from other countries, which show similar rates of free or total thyroid hormone testing …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations